Apakah Work-Life Balance dan Komitmen Afektif Memediasi Praktik Sumber Daya Manusia terhadap Kinerja UMK? - Desiana, Putri Mega; Cindi, Ramitha Janira (UI Scholars Hub, 2020)
Micro and Small Enterprises (MSEs) have an integral role in Indonesian society's growth and development, especially in the economic sector. This study aims to determine the mediating role of work-life balance and affective commitment to human resource practices and its impact on the performance of MSEs. Similar to large organizations, small organizations also implement HR practices, although they are still very simple, affecting the organization's performance. So far, work-life balance and affective commitment have been widely studied in large organizations and are considered essential in improving organizational performance. However, the role of work-life balance in improving small businesses' performance has not been widely studied. This study was conducted with a total of 134 respondents from MSEs in Jabodetabek. The analysis was carried out using structural equation modeling. Some interesting findings were found, the work-life balance, which usually has a positive effect turns out to have a negative and significant effect on the performance of MSEs. The reason is presumably because MSEs owners must do constant monitoring to continue smooth operational activities and increase organizational performance; hence the time spent in the workplace was increased.